THE DYNAMICS OF DIGITAL NATIVE COMMUNICATION BEHAVIOUR IN PESANTREN COMMUNITIES IN EAST LOMBOK - Andri Kurniawan (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2024)
The presence of digitalization in addition to supporting learning also has bad consequences when used disproportionately. The Covid-19 phenomenon requires students to use digitalization as an online learning medium. The existence of pesantren habitus with the dynamics of student media behavior is an interesting thing to discuss in this research which uses qualitative methods through case studies in several madrasahhs in the pesantren environment in East Lombok. The result of the study is that the behavioral dynamics that occur in students as digital natives are micro dynamics with the majority guided by values and norms in Pesantrens although some of them experience behavioral and communication dynamics due to the use of media including youtube and online games such as the use of slang language that is not in accordance with the habits of pesantren. Including as a positive and negative impact of media consumption.